Capitalising on income approach as trademark valuation for entrepreneurs - Mohd Ishan, Zahira; Noordin, Norrezan (Universiti Putra Malaysia Press, 2015)
The various valuation approaches that have been developed are meant for tangible assets valuation and are carried out by expert valuers. For intangible assets including trademarks, the international standards propose three main valuation approaches with the aim, among others, of better transparency and wider interest groups. These are the cost, market and income approaches. This paper suggests that the valuation of trademarks helps to reassure entrepreneurs that their trademarks are valuable assets. The entrepreneurs' competitiveness in the market is reassured when the trademarks are disclosed at fair value in the financial statements. This paper highlights the benefits of adopting the income approach for entrepreneurs, particularly the profit split method, by referring to several lculation methodologies as guidance for entrepreneurs in the valuation of trademarks.